Interactive effect of electron beam irradiation and montmorillonite (MMT) on properties of polycarbonate (PC)/acrylonitrile butadiene styrene (ABS) nanocomposites - Bee, Soo Tueen (Springer Verlag, 2019)
This research was conducted to investigate the effect of montmorillonite (MMT) content on the flame retardancy, physico-mechanical properties of electron beam irradiated polycarbonate (PC)/acrylonitrile butadiene styrene (ABS) blends. Based on this research, it is revealed that the increase in MMT loading level has gradually increased the flame retardancy and thermal stability of the flame retarded PC/ABS blends, which is due to the induction of char residues formed by the presence of MMT particles as measured in TGA analysis. Besides, the introduction of electron beam irradiation has gradually improved the flame retardancy (LOI) by forming crosslinking networks in PC/ABS blends (as evident by the increment in gel content) which restricts the permeability of volatile and air through the polymer matrix. The addition of low MMT amount (2 phr) has reduced the elongation at break which is attributed to the intercalation of polymer matrix into the interlayer galleries of MMT particles as evident by increment in d spacing. However, the higher amount of MMT particles tended to form agglomeration and thus reduced the tensile strength of flame retarded PC/ABS blends. The increase in irradiation dosages has gradually induced the Young’s modulus of flame retarded PC/ABS blends by forming crosslinking networks.